DETERMINING NUMBER AND LOCATION OF ELECTRIC BUS SHELTER IN GANESHA – JATINANGOR ROUTE WITH ANP (ANALYTIC NETWORK PROCESS) MODEL - Pratiwi, Nimas Rosyana; Lestari, Yuliani Dwi (Journal of Business and Management, 2018)
Abstract. Traffic congestion and pollution is an unsolved old issue in every major city. In fact, the second largest division in contributing to the emissions of carbon dioxide (CO2) is the transportation area, due to the ignition of the petroleum product. Currently, most of Indonesia larger cities had same problems related about transportation. Government now try to find a way how to increasing role of public transportation, decreasing usage of private cars, decreasing congestion, and decreasing number of road accidents. Indonesia government through NCSTT (National Center of Sustainable Technology Transportation) wants to implementing sustainable transportation in Indonesia. Electric Vehicle is one of their projects. The project will be conduct in Bandung City with focus on developing electric vehicle from ITB Ganesha to ITB Jatinangor. Electric vehicle is expected to be the back bone of public transportation in Bandung. It helps government to reduce the traffic congestion and also reduce the pollution. The data that is used in this study was collected from secondary data and primary data. The secondary data comes from the previous study while the primary data obtain from the direct observation that have been done on May 24th until July 3rd, 2018 and questionnaire that filled by expertise and distributed via paper based as well. To provide the electric bus, there are some supporting things, one of the is bus shelter. The research finds out that to build the bus shelter need location strategy. Analityc Hierarchy Process (AHP) is used to determine the best location for electric bus shelter with deliberate the factors which is distance, urban traffic, and availability of space. Hopefully this study can contribute to Indonesia government in implementing sustainable transportation and as reference for Bandung government and stakeholder in developing the infrastructure and commercialization area of the electric vehicle.Keywords: Sustainable Transportation, Electric Vehicle, Bus Stop, AHP